On-Treatment Improvement of MELD Score Reduces Death and Hepatic Events in Patients With Hepatitis B-Related Cirrhosis. (November 2018) - Yip, Terry; Chan, Henry; Tse, Yee-Kit; Lam, Kelvin; Lui, Grace; Wong, Vincent; Wong, Grace
Abstract Objectives Antiviral treatment modifies the natural history of chronic hepatitis B (CHB)-related cirrhosis as reflected by improving Model for End-Stage Liver Disease (MELD) score over time. We evaluated the impact of on-treatment change of MELD score on clinical outcomes in patients with CHB-related cirrhosis. Methods Cirrhotic CHB patients who received entecavir and/or tenofovir disoproxil fumarate for at least 6 months in Hong Kong between 2005 and 2016 were identified. The primary outcome was all-cause mortality; secondary outcomes were hepatocellular carcinoma (HCC), and hepatic events including ascites, spontaneous bacterial peritonitis, variceal bleeding, hepatorenal syndrome, hepatic encephalopathy, and liver transplantation. Results We identified 1743 cirrhotic CHB patients. Their mean MELD score decreased from 12.3 ± 5.5 at baseline to 11.0 ± 4.7 at month 6. At a median (interquartile range) follow-up of 3.9 (1.9–6.0) years, 290 (16.6%) patients died; 201 (11.5%) developed HCC. Among 1140 patients without prior hepatic events, 150 (13.2%) developed hepatic events. Among 464 patients with baseline MELD score ≥15, the 6-year cumulative mortality was 72.8, 36.7, and 23.1% for unchanged or increased MELD score, 1–5 point improvement in MELD score, and >5 point improvement in MELD score at month 6, respectively (log-rank test, P  < 0.001); the corresponding 6-year cumulative incidence of hepatic events was 52.7, 30.5, and 23.9% in the three subgroups (Gray's test, P  = 0.004). Patients with MELD score <15 at month 6 had lower risk of mortality and hepatic events (allP  < 0.001). Conclusions On-treatment improvement of MELD score correlates with reduced risk of mortality and hepatic events in cirrhotic CHB patients.